Advanced producer services and core–periphery trajectories in German metropolitan regions - Zöllner, Silke; Jüttner, Uta; Angus, Andrew (MDPI, 2026)
This paper examines how the growth and decline of agglomerations and peripheries in metropolitan regions can be understood in the context of Advanced Producer Service (APS) firm decisions, regional conditions and institutional policies. Focusing on Germany, it responds to divergent quantitative findings for Munich and Dresden and to outcome-oriented studies documenting spatial patterns, leaving underlying mechanisms under-specified. This study adopts an embedded qualitative case study design, analysing Munich and Dresden as contrasting metropolitan subunits within a shared national framework. Drawing on documentation, archival records and expert interviews with economic development and regional governance actors, it uses explanation building and template analysis to link empirical material to an analytical framework integrating firm, location and public authority perspectives. The results identify four recurrent configurations in the firm–location–policy nexus: reinforcing agglomeration, emerging limits to agglomeration, balancing peripheral growth and reinforced peripheral decline. These configurations show how the same metropolitan region can simultaneously exhibit core growth, constraints on further concentration, selective peripheral upgrading and cumulative peripheral disadvantage. Conceptually, this paper develops a mechanism-based account of APS-driven metropolitan development and proposes refined propositions that help reinterpret outcome-based studies on Munich and Dresden. More broadly, the configurations offer an analytical lens for analysing APS location dynamics and metropolitan governance challenges in other polycentric and federal contexts.
Keywords: advanced producer services; metropolitan regions; agglomeration; diffusion; core-periphery relations; firm-location-policy nexus; peripheralisation; Germany; Munich; Dresden; 33 Built Environment and Design; 44 Human Society; 3304 Urban and regional planning; 4406 Human geography; 4407 Policy and administration